Healthcare in Brazil: An Overview (British Journal of Multidisciplinary and Advanced Studies, 2024)
This study examines the present comprehension of healthcare in Brazil, which accounts for 9.3% of GDP and is not viable in the long term. The research enhances the caliber and triumph of private healthcare initiatives in Brazil, as well as the entire Brazilian healthcare system. Our findings indicate that there are consistent concerns about the public healthcare system deteriorating due to the pandemic while the private healthcare system is seen as costly and a "necessary evil." Professionals in the Brazilian private healthcare system is encountering widespread discontent due to inadequate resources to meet the needs of the people. This research offers recommendations for future investigations.